An auxiliary, membrane-based mechanism for nuclear migration in budding yeast - Kirchenbauer, Marisa; Liakopoulos, Dimitris (Molecular biology of the cell, 2013)
How nuclear shape correlates with nuclear movements during the cell cycle is poorly understood. We investigated changes in nuclear morphology during nuclear migration in budding yeast. In preanaphase cells, nuclear protrusions (nucleopodia [NP]) extend into the bud, preceding insertion of chromosomes into the bud neck. Surprisingly, formation of nucleopodia did not depend on the established nuclear migration pathways. We show that generation and maintenance of NP requires nuclear membrane expansion, actin, and the exocyst complex. Exocyst mutations cause nuclear positioning defects and display genetic interactions with mutations that deactivate astral microtubule-dependent nuclear migration. Cells that cannot perform DNA replication also fail to form nucleopodia. We propose that nuclear membrane expansion, DNA replication, and exocyst-dependent anchoring of the nuclear envelope to the bud affect nuclear morphology and facilitate correct positioning of nucleus and chromosomes relative to the cleavage apparatus.
Gesehen am 22.06.2022